A wideband and polarization-insensitive graphene-based metamaterial absorber. (February 2021) - Nickpay, Mohammad Reza; Danaie, Mohammad; Shahzadi, Ali
Abstract: The concept of a wideband and polarization-insensitive absorber based on graphene for terahertz (THz) applications is presented in this paper. To broaden the absorption bandwidth, we have combined two concentric rectangular rings with cross-shaped strips. These are located on a silicon substrate. The analysis of the proposed absorber is based on the impedance matching theory and finite difference time domain (FDTD) methods. The simulated results show that the proposed absorber has a wideband absorption. The obtained bandwidth for absorption coefficients of 0.9 and 0.7 are 16% and 20.3%, respectively over the range of 2.47–2.9 THz and 2.39–2.93 THz. The bandwidth and absorption performance of the absorber can be adjusted by the control of the conductivity of graphene by applying an external DC-bias voltage. Due to the symmetrical design of the structure, the presented absorber is polarization insensitive. Furthermore, due to having a cross-strip structure, the performance of the proposed absorber is insensitive to the angle of the radiant wave. Thus, the proposed absorber can be considered a suitable candidate for various THz applications. Highlights: A wideband and polarization-insensitive graphene absorber for terahertz (THz) applications is presented. The absorption bandwidths for 0.9 and 0.7 transmittances are 15.6% and 20.3%, respectively. To broaden the bandwidth, a combination of two concentric rectangular rings with cross-shaped strips are used. Due to the symmetrical design, the presented absorber is polarization insensitive. The bandwidth and absorption performance of the absorber can be adjusted by applying an external DC-bias voltage.